Abandoned buildings on old sugar mill of slave era, Jamaica. - Novelty Trading Co., Ltd. (Kingston : Novelty Trading Co., Ltd, 1966)
The image shows a young lady riding on a horse in front of a old sugar mill with two young children looking on. There is also a small river and tall coconut tree in the image.
Keywords: Sugar factories -- Jamaica; Postcards -- Jamaica